Blend of polyvinyl chloride and plasticizing and toughening agent and preparation method thereof

Through core-shell polycarbonate block copolymer blended with polyvinyl chloride, the problems of thermal processing difficulties of PVC materials and the carcinogenicity or high cost of plasticizers are solved, and better processing and mechanical properties are achieved, which is suitable for commercial applications.

CN119775685AActive Publication Date: 2025-04-08SUN YAT SEN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510274426.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-08
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

The existing polyvinyl chloride (PVC) materials exhibit brittle and hard properties due to the polar bond interactions of the chain segments, which are difficult to heat processing, and commonly used plasticizers have problems such as carcinogenicity or high cost and complex preparation process.

Method used

Core-shell polycarbonate block copolymer is used to blend with polyvinyl chloride to improve the processing and mechanical properties of PVC by adjusting the structure and molecular weight of the polymer.

Benefits of technology

It significantly improves the processing and mechanical properties of polyvinyl chloride, reduces the glass transition temperature, improves toughness and elongation at break, while maintaining tensile strength and transparency. This method is non-toxic and low-cost, and is suitable for large-scale commercial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775685A_ABST
    Figure CN119775685A_ABST
Patent Text Reader

Abstract

The invention discloses a blend of polyvinyl chloride and a plasticizing and toughening agent and a preparation method of the blend. Under the same mixing condition of the polycarbonate block copolymer and the polyvinyl chloride, the elastomer has more ester bonds and long-chain branches, so that compared with the existing commercialized toughening agent, the toughening agent has more excellent plasticizing and toughening effects, the processing performance of the polyvinyl chloride can be remarkably improved, the glass-transition temperature can be reduced, the toughness can be improved, and the service life of the toughening agent can be prolonged. The elongation at break of the polyvinyl chloride is obviously improved. Compared with the existing commercialized polyvinyl chloride toughening modifier, the polycarbonate block copolymer has the advantages of degradability, excellent toughening effect and lower preparation cost, has the advantages of no toxicity, difficulty in migration or leaching and the like due to high molecular weight, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and more specifically to a blend of polyvinyl chloride and a plasticizer and toughener and a preparation method thereof. Background Art

[0002] As a general-purpose plastic, polyvinyl chloride (PVC) has a huge and steadily growing market demand, and its consumption is second only to polyethylene. It is widely used in many fields such as medical devices, packaging, construction, toys, etc. Due to the interaction between the polar bonds C-Cl between PVC chains, the mobility of the chain segments is hindered, making it brittle and hard, and difficult to heat process, which limits its application.

[0003] PVC plastics usually cannot be used directly, and have poor thermal stability and impact strength. Appropriate plasticizers and tougheners need to be added to improve the processability, flexibility, impact resistance, etc. of PVC. Currently, commercial plasticizers such as phthalates (DOP) are banned due to their carcinogenicity. Dioctyl terephthalate (DOTP) is non-toxic and widely used as a substitute for DOP, but due to its low molecular weight, it also has the problem of easy migration. High molecular weight plasticizers and tougheners such as polyacrylates (ACR) and methyl methacrylate-butadiene-styrene copolymers (MBS) can better plasticize and toughen PVC and are not easy to migrate, but they have problems such as high cost and complex preparation process. Summary of the invention

[0004] The purpose of the present invention is to overcome the above defects and shortcomings in the prior art and provide a blend of polyvinyl chloride and a plasticizer and toughener obtained by modifying polyvinyl chloride using a core-shell polycarbonate block copolymer.

[0005] The above-mentioned object of the present invention is achieved through the following technical solutions: A blend of polyvinyl chloride and a plasticizer and toughener, wherein the plasticizer and toughener is a polycarbonate block copolymer, and the mass ratio of the polyvinyl chloride to the polycarbonate block copolymer is 100:5-100:60.

[0006] The structural formula of the polycarbonate block copolymer is as shown in formula (I) or formula (II), wherein a≥1, b≥1, c≥0, d≥1, e≥1, f≥0, n≥1; a, b, c, d, e, f, n are all integers, and R is H or Cl;

[0007]

[0008] Preferably, the molecular weight of the copolymer is in the range of 1000-200000Da, the molar content of polycarbonate in formula (I) is 70%-100%, the weight content of polycarbonate in formula (II) is 40%-90%, and the weight content of polyester is 60%-10%.

[0009] The preparation method of the polycarbonate block copolymer comprises the following steps: S1: Add the diinitiator, catalyst and allyl glycidyl ether into a high-pressure reactor under anhydrous and oxygen-free conditions, fill with carbon dioxide, and react for a period of time under magnetic stirring and heating conditions and then stop; S2-Ⅰ: After the reaction of S1 is completed, cyclohexene oxide is added under anhydrous and oxygen-free conditions, carbon dioxide is introduced, and the reaction is carried out under magnetic stirring and heating conditions. After the reaction is completed, the product is dissolved in dichloromethane and precipitated and purified in ethanol to obtain an intermediate of the product of formula (Ⅰ); S2-Ⅱ: After the reaction of S1 is completed, propylene oxide, phthalic anhydride or tetrachlorophthalic anhydride is added under anhydrous and oxygen-free conditions, and the reaction is carried out under magnetic stirring and heating conditions. After the reaction is completed, the product is dissolved in dichloromethane and precipitated and purified in ethanol to obtain an intermediate of the product of formula (Ⅱ); S3: The purified intermediate in S2 is dissolved in dichloromethane, and alkylthiol and photoinitiator are added. Under ultraviolet light radiation, the alkylthiol reacts with the double bond to form a long branched chain to obtain the final polymerization products of formula (I) and formula (II).

[0010] Preferably, the diinitiator in step S1 is a quaternary ammonium phthalate, the structure of which is shown in formula (III); the catalyst in step S1 is triethylboron, triphenylboron or tri(pentafluorophenyl)boron, and the molar ratio of the diinitiator, the catalyst and allyl glycidyl ether in step S1 is 1:5-20:500-5000; the reaction pressure of carbon dioxide in step S1 is 1-3MPa, the reaction temperature is 40-60°C, and the reaction time is 10-30h; the reaction in step S1 is bulk polymerization or solution polymerization, and the solution used for solution polymerization is toluene, n-hexane or tetrahydrofuran;

[0011] Preferably, in step S2-Ⅰ, the molar ratio of the cyclohexene oxide to the allyl glycidyl ether in S1 is 1-3:1, the reaction pressure of the carbon dioxide is 1-3 MPa, the temperature is 40-60° C., and the reaction time is 2-10 h; In step S2-II, the molar ratio of propylene oxide to phthalic anhydride or tetrachlorophthalic anhydride is 1:0.5-2, the molar ratio of the initiator to propylene oxide in S1 is 1:500-2000, the reaction temperature is 40-60°C, and the reaction time is 1-10h.

[0012] Preferably, the amount of alkylthiol added in step S3 is 1-1.4 times the number of C=C double bonds contained in the polymer, and the weight of the photoinitiator added is 0.1-0.5% of the weight of the polymer; the wavelength of the ultraviolet light is 360-365nm, and the light intensity is 35mW / cm 2 , the exposure time is 1-20min, and the reaction temperature is room temperature.

[0013] Preferably, the photoinitiator is 2,2-dimethoxy-2-acetophenone.

[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. Under the same mixing conditions, the blend of the polycarbonate block copolymer and polyvinyl chloride provided by the present invention has a better plasticizing and toughening effect than existing commercial toughening agents due to the presence of more ester bonds and long chain branches in the elastomer, and can significantly improve the processing performance of polyvinyl chloride, reduce the glass transition temperature, improve toughness, and significantly increase the elongation at break of polyvinyl chloride.

[0015] 2. The polycarbonate block copolymer prepared by the present invention is non-toxic, has a high molecular weight, is not easy to migrate or leach from the product body, and can maintain good tensile strength and high transparency while plasticizing and toughening polyvinyl chloride.

[0016] 3. The raw materials of the present invention are cheap bulk chemical raw materials, which contain carbon dioxide, have the advantages of rapid reaction, low cost, biodegradability, and green environmental protection, and are conducive to large-scale commercial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the hydrogen NMR spectrum of the polycarbonate block copolymer obtained in Example 1 of the present invention (deuterated chloroform is the solvent).

[0018] Figure 2 This is the H-NMR spectrum of the polycarbonate block copolymer obtained in Example 4 of the present invention (deuterated chloroform is the solvent).

[0019] Figure 3 This is the H-NMR spectrum of the polycarbonate block copolymer obtained in Example 5 of the present invention (deuterated chloroform is the solvent). DETAILED DESCRIPTION

[0020] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0021] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0022] Example 1. Preparation of polycarbonate block copolymer (CAC-1) Under anhydrous and oxygen-free conditions, 1mmol of quaternary ammonium phthalate, 10mmol of triphenylboron, 2000mmol of allyl glycidyl ether and 1500mmol of tetrahydrofuran were added to a high-pressure reactor in sequence, heated in an oil bath at 50°C, stirred magnetically, and carbon dioxide was introduced at a pressure of 2 MPa for 24 hours. After the reaction stopped, 6000mmol of cyclohexene oxide was added under anhydrous and oxygen-free conditions, heated in an oil bath at 50°C, and carbon dioxide was introduced at a pressure of 2 MPa for 6 hours. After the reaction was completed, the product was dissolved in dichloromethane, precipitated in ethanol to obtain the product, and dried in vacuum at 40°C for 24 hours.

[0023] After each step of the reaction, the original solution was taken for nuclear magnetic resonance spectroscopy ( 1 H NMR) test, the conversion of allyl glycidyl ether was calculated to be 55%, and the conversion of cyclohexene oxide was 22%.

[0024] The dried intermediate was dissolved in dichloromethane, the number of double bonds was calculated according to the conversion rate of allyl glycidyl ether, 1.2 times of n-butyl mercaptan and 0.2 wt% of photoinitiator 2,2-dimethoxy-2-acetophenone were added, and the core-shell polycarbonate block copolymer CAC-1 with the structure of formula (IV) was obtained under ultraviolet irradiation for 20 min. The hard segment ratio was calculated to be 34 wt% according to the nuclear magnetic hydrogen spectrum. The gel permeation chromatography (GPC) test results showed that the number average molecular weight Mn was 64.6 KDa and the polymer dispersibility index PDI was 2.07. The nuclear magnetic hydrogen spectrum of the obtained polycarbonate block copolymer (deuterated chloroform as solvent) is as follows: Figure 1 shown. .

[0025] Example 2. Preparation of polycarbonate block copolymer (CAC-2) Under anhydrous and oxygen-free conditions, 1mmol quaternary ammonium phthalate, 12mmol triethyl boron, 2500mmol allyl glycidyl ether and 1500mmol tetrahydrofuran were added to the autoclave in sequence, heated in an oil bath at 45°C, stirred magnetically, and carbon dioxide was introduced at a pressure of 1 MPa for 22 hours. After the reaction stopped, 4000mmol cyclohexene oxide was added under anhydrous and oxygen-free conditions, heated in an oil bath at 55°C, and carbon dioxide was introduced at a pressure of 2 MPa for 10 hours. After the reaction was completed, the product was dissolved in dichloromethane, precipitated in ethanol to obtain the product, and dried in vacuum at 40°C for 24 hours.

[0026] After each step of the reaction, the original solution was taken for nuclear magnetic resonance spectroscopy ( 1H NMR) test, the conversion of allyl glycidyl ether was calculated to be 60%, and the conversion of cyclohexene oxide was 25%.

[0027] The dried intermediate was dissolved in dichloromethane, the number of double bonds was calculated according to the conversion rate of allyl glycidyl ether, 1.3 times of n-butyl mercaptan and 0.4 wt% of photoinitiator 2,2-dimethoxy-2-acetophenone were added, and the polymerization product CAC-2 with the structure of formula (IV) was obtained under ultraviolet light irradiation for 10 min. The hard segment ratio was calculated to be 48 wt% according to the nuclear magnetic hydrogen spectrum. The gel permeation chromatography (GPC) test results showed that the number average molecular weight Mn was 75.7 KDa and the polymer dispersibility index PDI was 1.38.

[0028] Example 3. Preparation of polycarbonate block copolymer (CAC-3) Under anhydrous and oxygen-free conditions, 1mmol quaternary ammonium phthalate, 8mmol tris(pentafluorophenyl)boron, 2000mmol allyl glycidyl ether and 1200mmol tetrahydrofuran were added to a high-pressure reactor in sequence, heated in an oil bath at 50°C, stirred magnetically, and carbon dioxide was introduced at a pressure of 1.5 MPa for 24 hours. After the reaction stopped, 5000mmol cyclohexene oxide was added under anhydrous and oxygen-free conditions, heated in an oil bath at 50°C, carbon dioxide was introduced at a pressure of 2 MPa, and the reaction was continued for 10 hours. After the reaction was completed, the product was dissolved in dichloromethane, precipitated in ethanol to obtain the product, and dried in vacuum at 40°C for 24 hours.

[0029] After each step of the reaction, the original solution was taken for nuclear magnetic resonance spectroscopy ( 1 H NMR) test, the conversion rate of allyl glycidyl ether was calculated to be 50%, and the conversion rate of cyclohexene oxide was 25%.

[0030] The dried intermediate was dissolved in dichloromethane, the number of double bonds was calculated according to the conversion rate of allyl glycidyl ether, 1.2 times of dodecanethiol and 0.3wt% of photoinitiator 2,2-dimethoxy-2-acetophenone were added, and the polymerization product CAC-3 with the structure of formula (V) was obtained under ultraviolet light irradiation for 20 min. The hard segment ratio was calculated to be 34 wt% according to the nuclear magnetic hydrogen spectrum. The gel permeation chromatography (GPC) test results showed that the number average molecular weight Mn was 98.5KDa and the polymer dispersibility index PDI was 1.51.

[0031] .

[0032] Example 4. Preparation of polycarbonate block copolymer (PAP) Under anhydrous and oxygen-free conditions, 1mmol quaternary ammonium phthalate, 10mmol triphenylboron, 2000mmol allyl glycidyl ether and 1500mmol tetrahydrofuran were added to a high-pressure reactor in sequence, heated in an oil bath at 50°C, magnetically stirred, and carbon dioxide was introduced at a pressure of 2 MPa for 24 hours. After the reaction stopped, 800mmol propylene oxide and 1600mmol phthalic anhydride were added under anhydrous and oxygen-free conditions, heated in an oil bath at 50°C, and reacted for 4 hours. After the reaction was completed, the product was dissolved in dichloromethane, precipitated in ethanol to obtain the product, and dried in vacuum at 40°C for 24 hours.

[0033] After each step of the reaction, the original solution was taken for nuclear magnetic resonance spectroscopy ( 1 H NMR) test, it was calculated that the conversion rate of allyl glycidyl ether was 55%, the conversion rate of propylene oxide was 93%, and the conversion rate of phthalic anhydride was 45%.

[0034] The dried intermediate was dissolved in dichloromethane, the number of double bonds was calculated according to the conversion rate of allyl glycidyl ether, 1.2 times of n-butyl mercaptan and 0.4 wt% of the photoinitiator 2,2-dimethoxy-2-acetophenone were added, and the polymer product PAP with the structure of formula (VI) was obtained under ultraviolet light irradiation for 20 min. The hard segment ratio was calculated to be 38 wt% according to the nuclear magnetic hydrogen spectrum. The gel permeation chromatography (GPC) test results showed that the number average molecular weight Mn was 68.1 KDa and the polymer dispersibility index PDI was 2.11. The nuclear magnetic hydrogen spectrum of the obtained polycarbonate block copolymer (deuterated chloroform as solvent) is as follows: Figure 2 shown.

[0035]

[0036] Example 5. Preparation of polycarbonate block copolymer (TAT) Under anhydrous and oxygen-free conditions, 1mmol quaternary ammonium phthalate, 10mmol triethylboron, 2000mmol allyl glycidyl ether and 2000mmol tetrahydrofuran were added to a high-pressure reactor in sequence, heated in an oil bath at 45°C, magnetically stirred, and carbon dioxide was introduced at a pressure of 2 MPa for 36 hours. After the reaction stopped, 500mmol propylene oxide and 500mmol tetrachlorophthalic anhydride were added under anhydrous and oxygen-free conditions, heated in an oil bath at 50°C, and reacted for 6 hours. After the reaction was completed, the product was dissolved in dichloromethane, precipitated in ethanol to obtain the product, and dried in vacuum at 40°C for 24 hours.

[0037] After each step of the reaction, the original solution was taken for nuclear magnetic resonance spectroscopy ( 1 H NMR) test, it was calculated that the conversion rate of allyl glycidyl ether was 56%, the conversion rate of propylene oxide was 97%, and the conversion rate of phthalic anhydride was 95%.

[0038] The dried intermediate was dissolved in dichloromethane, the number of double bonds was calculated according to the conversion rate of allyl glycidyl ether, 1.2 times of n-butyl mercaptan and 0.4 wt% of the photoinitiator 2,2-dimethoxy-2-acetophenone were added, and the polymer product TAT with the structure of formula (VII) was obtained under ultraviolet irradiation for 20 min. The hard segment ratio was calculated to be 35 wt% according to the nuclear magnetic hydrogen spectrum. The gel permeation chromatography (GPC) test results showed that the number average molecular weight Mn was 65.6 KDa and the polymer dispersibility index PDI was 2.08. The nuclear magnetic hydrogen spectrum of the obtained polycarbonate block copolymer (deuterated chloroform as solvent) is as follows: Figure 3 shown.

[0039]

[0040] Example 6. Plasticization and toughening of PVC using synthetic polycarbonate block copolymers The polycarbonate block copolymer synthesized in Example 1, Example 2, Example 3, Example 4 and Example 5 was melt blended with polyvinyl chloride in a Haake blender, the blending temperature was 180°C, the addition amount of calcium zinc composite heat stabilizer was 3 phr, and the melt blending time was 5 min. The mechanical properties and glass transition temperature test results of the blends are listed in Table 1.

[0041] Commercially available plasticizers and tougheners MBS and ACR were melt-blended with polyvinyl chloride. The experimental method and test method were the same as those in Example 6. The test results of the mechanical properties and glass transition temperature of the blends are listed in Table 1.

[0042]

[0043] It can be seen from Table 1 that the polyester copolymer synthesized by the present invention is used as a plasticizer for polyvinyl chloride. After plasticization at a certain ratio, the blend exhibits good plasticity, has higher elongation at break and tensile strength than commercial MBS and ACR, and has a significantly lower glass transition temperature than the experimentally measured 84.6°C of pure PVC and 86.3°C of comparative PVC / ACR, showing good plasticizing and toughening effects, and can greatly reduce the processing temperature.

Claims

1. A blend of polyvinyl chloride and a plasticizer and toughener, comprising polyvinyl chloride and a plasticizer and toughener, characterized in that The plasticizer and toughener is a polycarbonate block copolymer, and the mass ratio of polyvinyl chloride to the polycarbonate block copolymer is 100:5-100:60; the structural formula of the polycarbonate block copolymer is as shown in formula (I) or formula (II), wherein a≥1, b≥1, c≥0, d≥1, e≥1, f≥0, n≥1; a, b, c, d, e, f, n are all integers, and R is H or Cl; 。 2. The blend of polyvinyl chloride and a plasticizer and toughener as claimed in claim 1, characterized in that The molecular weight of the copolymer is in the range of 1000-200000Da, the molar content of polycarbonate in formula (I) is 70%-100%, the weight content of polycarbonate in formula (II) is 40%-90%, and the weight content of polyester is 60%-10%.

3. The blend of polyvinyl chloride and a plasticizer and toughener as claimed in claim 1, characterized in that The preparation method of the polycarbonate block copolymer comprises the following steps: S1: Add the diinitiator, catalyst and allyl glycidyl ether into a high-pressure reactor under anhydrous and oxygen-free conditions, fill with carbon dioxide, and react for a period of time under magnetic stirring and heating conditions and then stop; S2-Ⅰ: After the reaction of S1 is completed, cyclohexene oxide is added under anhydrous and oxygen-free conditions, carbon dioxide is introduced, and the reaction is carried out under magnetic stirring and heating conditions. After the reaction is completed, the product is dissolved in dichloromethane and precipitated and purified in ethanol to obtain an intermediate of the product of formula (Ⅰ); S2-Ⅱ: After the reaction of S1 is completed, propylene oxide, phthalic anhydride or tetrachlorophthalic anhydride is added under anhydrous and oxygen-free conditions, and the reaction is carried out under magnetic stirring and heating conditions. After the reaction is completed, the product is dissolved in dichloromethane and precipitated and purified in ethanol to obtain an intermediate of the product of formula (Ⅱ); S3: The purified intermediate in S2 is dissolved in dichloromethane, and alkylthiol and photoinitiator are added. Under ultraviolet light radiation, the alkylthiol reacts with the double bond to form a long branched chain to obtain the final polymerization products of formula (I) and formula (II).

4. The blend of polyvinyl chloride and a plasticizer and toughener as claimed in claim 3, characterized in that The bi-initiator described in step S1 is a quaternary ammonium phthalate, and its structure is shown in formula (III); the catalyst described in step S1 is triethylboron, triphenylboron or tri(pentafluorophenyl)boron, and the molar ratio of the bi-initiator, the catalyst and allyl glycidyl ether described in step S1 is 1:5-20:500-5000; the reaction pressure of carbon dioxide described in step S1 is 1-3MPa, the reaction temperature is 40-60°C, and the reaction time is 10-30h; the reaction in step S1 is bulk polymerization or solution polymerization, and the solution used for solution polymerization is toluene, n-hexane or tetrahydrofuran; 。 5. The blend of polyvinyl chloride and a plasticizer and toughener as claimed in claim 3, characterized in that In step S2-Ⅰ, the molar ratio of the cyclohexene oxide to the allyl glycidyl ether in S1 is 1-3:1, the reaction pressure of the carbon dioxide is 1-3 MPa, the temperature is 40-60° C., and the reaction time is 2-10 h; In step S2-II, the molar ratio of propylene oxide to phthalic anhydride or tetrachlorophthalic anhydride is 1:0.5-2, the molar ratio of the initiator to propylene oxide in S1 is 1:500-2000, the reaction temperature is 40-60°C, and the reaction time is 1-10h.

6. The blend of polyvinyl chloride and a plasticizer and toughener as claimed in claim 3, characterized in that In step S3, the amount of alkylthiol added is 1-1.4 times the number of C=C double bonds contained in the polymer, and the weight of the photoinitiator added is 0.1-0.5% of the weight of the polymer; the wavelength of the ultraviolet light is 360-365nm, and the light intensity is 35mW / cm 2 , the exposure time is 1-20min, and the reaction temperature is room temperature.

7. The blend of polyvinyl chloride and a plasticizer and toughener as claimed in claim 3, characterized in that The photoinitiator is 2,2-dimethoxy-2-acetophenone.

Citation Information

Patent Citations

  • Preparation method of polyester plasticizer

    CN106554490A

  • Biodegradable copolymer for plasticizing and toughening polyvinyl chloride and preparation method thereof

    CN115044024A

  • Polycarbonate type plasticizer

    CN119039578A

  • Environment-friendly macromolecular modified PVC (polyvinyl chloride) composition

    CN119570176A